An Ethical Perspective on CEO Compensation - Perel, Mel (Journal of business ethics, 2003)
The controversial issue of whether Chief Executive Officer (CEO) compensation is excessive or appropriate is examined in terms of two competing claims: that CEOs are overpaid for the value they provide to an enterprise, and that CEO compensation is inherently equitable. Various arguments and perspectives on both sides of the issue are assessed. Little evidence supports the claim that CEO performance justifies very high compensation. Further, the complex interactive alliance between boards of directors and CEOs compromises rational decision-making about CEO compensation, with the Enron affair offered as an illustration of what can go wrong when dishonest CEO actions combine with lax board oversight. Recommendations for restoring trust in the system include continuing current regulatory actions, using different metrics for determining CEO compensation, making board member-CEO relationships transparent to all company stakeholders, and several more radical ideas for change. Stakeholders must resist being distracted by other social, economic, or political issues from pursuing serious, lasting reform.